2018
DOI: 10.3892/ol.2018.7777
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ induces the upregulation of RFXAP via inhibition of miR-212-3p in pancreatic cancer cells: A novel mechanism for IFN-γ response

Abstract: Abstract. Previous studies have demonstrated that pancreatic cancer-derived microRNA (miR)-212-3p can inhibit the expression of regulatory factor X-associated protein (RFXAP), an important transcription factor for major histocompatibility complex (MHC) class II, and thereby lead to downregulation of MHC class II in dendritic cells. It has also been established that interferon (IFN)-γ can increase the expression of MHC class II in immune cells. It was therefore hypothesized that IFN-γ can inhibit miR-212-3p exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Therefore, new trials are encouraged to further develop and verify our risk signature in standard treatment cohorts. Emerging evidence have confirmed the prognostic values of immune genes in various cancers (Patel et al, 2013;Surmann et al, 2015;Yang et al, 2015;Ling et al, 2017;Ding et al, 2018). In current study, six IRGs were identified as the risk signature.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Therefore, new trials are encouraged to further develop and verify our risk signature in standard treatment cohorts. Emerging evidence have confirmed the prognostic values of immune genes in various cancers (Patel et al, 2013;Surmann et al, 2015;Yang et al, 2015;Ling et al, 2017;Ding et al, 2018). In current study, six IRGs were identified as the risk signature.…”
Section: Discussionsupporting
confidence: 69%
“…It was revealed to downregulate the expression of MHC class II in DCs (Ding et al, 2015) and macrophages (Wu et al, 2019), resulting inhibition of CD4 + T cells infiltration (Surmann et al, 2015). It was associated with survival outcomes in solid tumors (Surmann et al, 2015;Ding et al, 2018). Overall, the prognostic values of the six risk genes have been exploited in various cancers, and their contribution to immune regulations were mainly concentrated on antigen presenting cells and effector T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, although miR-212-3p was reported to be associated with various types of cancers such as bladder cancer, glioma, sarcoma and pancreatic cancers (Wu et al 2019 ; Liu et al 2015 ; Ding et al 2018 ; Xie et al 2018 ), its association with BC was not well understood. One weak association was that the BC resistance protein (BCRP/ABCG2) was under regulation of miR-212-3p in renal cancer cells (Reustle et al 2018 ), the regulation of miR-212-3p in BC was merely mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-derived and endogenous exosomal miRNAs can regulate cross-presentation in dendritic cells and with other immune cells, this exomsomal miRNAs-mediated intercellular communication may affect the maturation of DCs [143,144]. In pancreatic cancer, exosomal miR-212-3p targets MHC class II TF RFXAP resulting in reduced expression of HLA-DR, -DP, and -DQ molecules and thus interfering with the function of DCs cells [145,146]. Exosomal miR-203 is able to reduce the expression of TLR4, TNF-α and IL-12 in DCs, affecting the activation of natural killer cells (NKs) [147].…”
Section: Promoting the Formation Of Immunosuppressive Environmentmentioning
confidence: 99%